Eating Disorders and Depression in Adolescents: The Impact of Socioeconomic Factors, Family and Peer Relations - Livazović, Goran; Mudrinić, Iva (International Journal of Child Health and Nutrition, 2018)
This paper analyses the relation between socioeconomic characteristics, family and peer relations, depression and eating disorders with 218 (144 female, 66.1%) participants aged 14-19 from Croatia. The questionnaire encompassed questions on socioeconomic traits, family and peer relations, depression and anorexia, bulimia, binge eating and orthorexia. Girls reported most dissatisfaction with the abdominal region (38.5%), thighs (31.2%) and breasts (16.1%). Boys reported most dissatisfaction with the abdomen (12.4%), chest (10.1%) and legs/calves (7.3%). Gender was significant for depression (p<.001), anorexia (p<.01), bulimia (p<.001) and binge eating (p<.05), with girls scoring higher on all scales. Age was significant for depression (p<.05) in younger participants, and orthorexia (p<.05) for older adolescents. Participants from vocational schools reported significantly higher family life satisfaction (p<.01), while gymnasium students reported significantly higher depression (p<.000), bulimia (p<.01) and binge eating behaviour (p<.01). Higher mother’s educational level was significant for anorexia (p<.05) and orthorexia (p<.01). Family relations correlated negatively with bulimia and binge eating, but positively with orthorexia. Peer relations were not significant for eating disorders. Eating disorders show positively correlated comorbidity (p<.000), and were significantly correlated to depression (p<.000). Anorexia is best predicted by bulimia (p<.001), orthorexia (p<.001), depression (p<.01) and mother’s education (p<.01). Bulimia is strongly predicted by anorexia (p<.001), binge eating (p<.001), depression (p<.001) and gender (p<.001). Binge eating is strongly predicted by bulimia (p<.001), depression (p<.01) and school type (p<.05). Orthorexia is strongly predicted by anorexia (p<.001), family relations quality (p<.05), the mother’s education (p<.05) and school success (p<.05).